2019
DOI: 10.1186/s41118-018-0046-6
|View full text |Cite
|
Sign up to set email alerts
|

Childbearing intentions in a low fertility context: the case of Romania

Abstract: This paper applies the Theory of Planned Behaviour (TPB) to find out the predictors of fertility intentions in Romania, a low-fertility country. We analyse how attitudes, subjective norms and perceived behavioural control relate to the intention to have a child among childless individuals and one-child parents. Principal axis factor analysis confirms which items proposed by the Generation and Gender Survey (GGS 2005) act as valid and reliable measures of the suggested theoretical socio-psychological factors. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
1
11
0
5
Order By: Relevance
“…5,17 In particular, the number of children is the best priority variable, which implies that childcare is a highly significant burden. 18 This study supports earlier literature from Romania 19 and Sweden. 20…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…5,17 In particular, the number of children is the best priority variable, which implies that childcare is a highly significant burden. 18 This study supports earlier literature from Romania 19 and Sweden. 20…”
Section: Discussionsupporting
confidence: 87%
“…Childbearing intentions regarding a second child include more factors based on one’s experience. 19,21 In this study, participants with one child were positively connected to a system with fringe benefits of reduced working time during the childcare period. Denmark successfully overcame low birth rates by creating a working environment that enables parents to spend more time with their children.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this argument, an increasing array of studies has linked socio-economic circumstances to childlessness. A greater prevalence of childlessness is documented for higher educated and working women (Burkimsher and Zeman, 2017 for Austria and Switzerland; Berrington, 2017 for the UK; Köppen et al, 2017 for France;Reher and Requena, 2019 for Spain;Mynarska et al, 2015 for Italy and Poland;Hoem et al, 2006 for Sweden;Abma and Martinez, 2006;Hayford, 2013 for the US), who also report greater intentions to be childless (Miettinen et al, 2015;Ciritel et al, 2019 for Romania; Biryukova and Tyndyk, 2015 for Russia). 1 If the review of the empirical research on childlessness seeks to position explanations for it into discourses in line with the economic arguments, counterintuitive empirical evidence also suggests that economic factors alone might not be enough for understanding the mechanisms that work behind childlessness.…”
Section: Fertility Childlessness and The New Home Economics Perspecmentioning
confidence: 99%
“…A birth intention survey showed that women with more economic and social resources were more likely to have a second child [ 13 ]. However, another study indicated that income was not a deciding factor for planning to have a child [ 14 ]. The findings of the relationship between fertility ideation and economic aspects were mixed in the existing literature.…”
Section: Introductionmentioning
confidence: 99%